PERAN DAMKAR SEBAGAI UPAYA PELAYANAN PEMADAM KEBAKARAN DAN PENYELAMATAN DINAS PEMADAM KEBAKARAN DI KECAMATAN LONGKALI KABUPATEN PASER - Risky Noviar; Muh. Jamal; Muhlis Hafel (Halu Oleo University, 2023)
This research was conducted to determine the role of the Longkali District Fire Unit in supporting the Paser Regency Fire Service and identifying inhibiting factors and supporting factors for fire services in the Longkali District. This research uses qualitative research methods using primary data and secondary data with data collection techniques through interviews, document studies, and direct observation so that the role of the Longkali District Fire Department is described. The District Fire Department (Damkar) was greatly helped by the existence of a Fire Task Force in the District, especially in Longkali District. With the condition of a large area and the position of Longkali District, it is the outermost district bordering PPU Regency so coordination is always carried out whether it is when a fire occurs or fire anticipation and prevention activities. However, with the limited personnel and facilities, and infrastructure, the role of the Longkali District Fire Task Force is seen as very helpful to the duties and functions of the District Damkar. There are several inhibiting factors and there are also supporting factors for the Longkali District Fire Task Force in carrying out its role so that researchers provide some suggestions or inputs to overcome these inhibiting factors including by forming volunteers in each village. Coordinating with the nearest Fire Task Force and improving skills for personnel by including education and training to add insight and ability. Optimizing existing budgets and trying to get additional budgets both sourced from government and private budgets.